Uptake and storage of vitamin A as lipid droplets in the cytoplasm of cells in the lamina propria mucosae of the rat intestine. (9th July 2013) - Senoo, Haruki; Mezaki, Yoshihiro; Morii, Mayako; Hebiguchi, Taku; Miura, Mitsutaka; Imai, Katsuyuki
Abstract Vitamin A (retinyl palmitate) was injected subcutaneously or administered to rats by tube feeding. After subcutaneous injection, vitamin A was taken up and stored in cells of the lamina propria mucosae of the rat intestine. After oral administration, vitamin A was absorbed by the intestinal absorptive epithelial cells and transferred to cells of the lamina propria mucosae, where cells took up and stored the transferred vitamin A. The morphology of these cells was similar to that of hepatic stellate cells (also called vitamin A‐storing cells, lipocytes, interstitial cells, fat‐storing cells or Ito cells). Thus, these cells in the intestine could take up vitamin A from the systemic circulation and as well as by intestinal absorption, and store the vitamin in the lipid droplets in their cytoplasm. The data suggest that these cells are extrahepatic stellate cells of the digestive tract that may play roles in both the absorption and homeostasis of vitamin A.